Analysis of pentagon fraud elements in detecting financial reporting fraud in healthcare companies - Riko Aldi Winata; Fitria Fertha Agustina; Naufal Sinatria; Andi Mulyono (Institute of Accounting Research and Novation (IARN), 2025)
The objective of this research was to analyse the influence of the fraud pentagon elements on the detection of financial reporting fraud in healthcare companies listed on the Indonesia Stock Exchange between 2021 and 2023. The elements examined included pressure (financial targets), opportunity (ineffective monitoring), rationalisation (change in auditor), competence (change in director) and arrogance (frequent number of CEO’s pictures). The study population includes 35 healthcare companies listed on the Indonesia Stock Exchange. Using purposive sampling and a time series method, resulting in 33 sample data. The study was conducted from April to June 2025 and analyzed using multiple linear regression. The results showed that financial targets and ineffective monitoring significantly influenced financial statement fraud, while change in auditor, change in director, and frequent number of CEO’s pictures showed no significant influence on financial statement fraud. These results support the fraud pentagon's function in detecting fraud and provide regulators and auditors with a point of reference for efforts to avoid fraud in the healthcare industry.